THE USE OF DIGITAL TECHNOLOGIES IN THE TRAINING PROCESS OF ARCHERS (Physical Culture and Sport: Scientific Perspective, 2024)
The use of digital technologies in sports is becoming increasingly widespread and opens up many opportunities to improve the training process, analyze data, and increase performance. Purpose: To reveal the benefits of using digital technologies in the training process of archers. Participants: 23 archers (age 13-14 years old) engaged in archery at the KZ “Kharkiv City Specialized Children’s and Youth Sports School of the Olympic Archery Reserve ‘KOMUNAR’” (Kharkiv). The experiment was conducted for 2 months from April to May 2024. At the beginning and at the end of the experiment, a survey was conducted in an interactive form using a Google form. Methods: Statistical analysis. The research used the method of mathematical statistics using the Microsoft Excel program to determine the arithmetic mean. Using SPSS Statistic 26, questionnaire results were compared using the xi-square test to test the mutual independence of the two connectivity table variables. Results: The survey showed that young athletes see value in the introduction of digital technologies that allow athletes to collect detailed data about their training and performances. The use of virtual reality creates an interesting and meaningful atmosphere that helps athletes immerse themselves in the training process and forget about stress. Mobile applications help archers track their progress, which contributes to a sense of real achievement, boosting self-confidence and having a positive impact on their psychological state. Digital platforms allow athletes from different parts of the world to train together online, which creates a sense of community and support, which also has a positive effect on their psychological state. Conclusions: The use of a special Score Keeper program, the Ianseo Scorekeeper application, and an augmented reality program in the training and competition process of archery is a necessary step in the development of this sport. Digital technologies provide significant advantages in efficiency and accessibility, which are key to the overall development of athletes.
Keywords: archery; digital in sports; augmented reality in sports; mobile applications in sports